Transcriptome analysis of Gossypium reveals the molecular mechanisms of Ca2+ signaling pathway on arsenic tolerance induced by arbuscular mycorrhizal fungi - Gong, Minggui; Bai, Na; Su, Jiajie; Wang, Yuan; Wei, Yanan; Zhang, Qiaoming (Frontiers in Microbiology, 2024)
Arbuscular mycorrhizal fungi (AMF) have been demonstrated their ability to enhance the arsenic (As) tolerance of host plants, and making the utilization of mycorrhizal plants a promising and practical approach for remediating Ascontaminated soils.. However, comprehensive transcriptome analysis to reveal the molecular mechanism of As tolerance in the symbiotic process between AMF and host plants is still limited. In this study, transcriptomic analysis of Gossypium seedlings was conducted with four treatments: non-inoculated Gossypium under non-As stress (CK0), non-inoculated Gossypium under As stress (CK100), F. mosseae-inoculated Gossypium under non-As stress (FM0), and F. mosseae-inoculated Gossypium under As stress (FM100). Our results showed that inoculation with F. mosseae led to a reduction in net fluxes of Ca 2+ , while increasing Ca 2+ contents in the roots and leaves of Gossypium under the same As level in soil. Notably, 199 and 3129 differentially expressed genes (DEGs) were specially regulated by F. mosseae inoculation under As stress and non-As stress, respectively. Through Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation and enrichment analyses, we found that under As stress, F. mosseae inoculation upregulated a significant number of genes related to the Ca 2+ signaling pathway genes, involved in cellular process, membrane part, and signal transduction. This suggests a potential role in mitigating As tolerance in Gossypium seedlings. Furthermore, our analysis identified specific DEGs in transcription factor families, including ERF, MYB, NAC, and WRKY, , that were upregulated by F. mosseae inoculation.